Software systems architecture : working with stakeholders using viewpoints and perspectives - Rozanski, Nick.; Woods, Eoin. (Upper Saddle River, NJ : Addison-Wesley, 2005)
Rozanski and Woods explain what software architecture is all about, and why the architect's role is vitally important to successful project delivery. This practical, practitioner-oriented guide explains how to design successful architectures for information systems and to see these through to their successful implementation.
Introduction -- Software Architecture Concepts -- Viewpoints and Views -- Architectural Perspectives -- The Role of the Software Architect -- Introduction to the Software Architecture Process -- The Architecture Definition Process -- Scope, Concerns, Principles, and Constraints -- Identifying and Engaging Stakeholders -- Identifying and Using Scenarios -- Using Styles and Patterns -- Producing Architectural Models -- Creating the Architectural Description -- Validating the Architecture -- Introduction to the Viewpoint Catalog -- The Functional Viewpoint -- The Information Viewpoint -- The Concurrency Viewpoint -- The Development Viewpoint -- The Deployment Viewpoint -- The Operational Viewpoint -- Achieving Consistency across Views -- Introduction to the Perspective Catalog -- The Security Perspective -- The Performance and Scalability Perspective -- The Availability and Resilience Perspective -- The Evolution Perspective -- Other Perspectives -- Working as a Software Architect -- Appendix: Other Viewpoint Sets -- Bibliography -- Index.
Includes bibliographical references (p. 523-529) and index.
1
Keywords: CIT; Computer software -- Development; Computer architecture